Failure Law and Mechanism of the Rock-Loose Coal Composite Specimen under Combined Loading Rate - Genshui Wu; Weijian Yu; Ze Liu; Zhu Tang (Advances in Civil Engineering)
The surrounding rock deformation in the underground mining roadway increases rapidly during excavation and mining disturbance. The semirock and coal roadway, which is formed by the rock and coal composite system, will show different mechanical properties. Therefore, loading rate and anchoring or not are critical to grasp the stability law of the rock-coal combination system under different conditions. The uniaxial mechanical test under the constant loading rate and combined loading rate is carried out in the static loading range (0.01∼10 mm·min−1) of the rock-loose coal composite specimen (RCCS). The test results show that the rock and loose coal composite specimen without bolt (RCB(0) specimen) are abnormal, and the uniaxial compressive strength (UCS) and residual strength (RS) of the specimen do not increase but decrease with the increase of loading rate. In contrast, the UCS of the rock-loose coal composite specimen with the bolt (RCB(1∼2) specimen) is consistent with that of the ordinary hard and brittle rock, which increases with the increase of loading rate. To a certain extent, the initial damage and the development of microcracks in loose coal bodies are limited by bolts. Finally, the deformation mechanism and constitutive equation of the rock-loose coal composite system are discussed.